Catalysts and inhibitors of critical transitions in ecological systems - Yuguang Yang; György Barabás; Serguei Saavedra; Aming Li (Proceedings of the National Academy of Sciences, 2026)
Ecological systems can experience sudden and often irreversible regime shifts, also known as critical transitions, with major consequences such as desertification, locust outbreaks, and coral reef collapse. Anticipating these shifts is a central challenge, particularly under accelerating climate change. Although early warning signals of critical transitions have been widely studied, the mechanisms that drive or prevent them remain less well understood. Here, we develop a theoretical framework based on time-delayed dynamics that allows us to identify processes acting as catalysts or inhibitors of critical transitions in ecological systems. We show that a composite measure combining time-delayed species interactions with species abundances is a key modulator of critical transitions. Beyond the critical point, systems exhibit persistent abundance oscillations, substantially increasing the risk of large-scale destabilization and species extinctions. Additionally, we show that a high diversity of species interaction types can act as a buffer of critical transitions. Instead, strong species self-regulation effects can act as catalysts of such transitions, contrary to common expectations. We illustrate the framework with empirical data from microbial systems. Together, these results provide a formal platform for exploring and understanding the drivers of critical transitions in complex living systems.